Effect of follicular fluid supplementation during in vitro maturation on total cell number in bovine blastocysts produced in vitro - Coelho Cruz, Maria Helena [UNESP]; Saraiva, Naiara Zoccal [UNESP]; Cruz, Jurandir Ferreira da; Oliveira, Clara Slade [UNESP]; Del Collado, Maite [UNESP]; Fernandes, Hugo; Castro, Fernanda Cavallari de; Garcia, Joaquim Mansano [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2014)
This study evaluated the influence of follicular fluid (FF) added to the maturation medium on the quality of bovine embryos produced in vitro. In the first experiment, oocytes were matured in media containing five different FF concentrations with different maturation times and classified according to meiotic progression and migration of cortical granules. In the second experiment, oocytes matured in the same media were fertilized at three different maturation times; thereafter, cleavage and blastocyst rates were evaluated. In the third experiment, oocytes were matured in media containing three different FF concentrations at two different maturation times, and embryo quality, inferred by the ratio of inner cell mass and trophectoderm cells compared with total cell number, was evaluated. Higher FF concentration (75 - 100% FF) slowed meiotic progression and CG migration (control - 78.13% vs. treated - 52.58% and control - 52.7% vs. treated - 11.59%, respectively, at 24 h of maturation). Also, FF at concentration of 75% or 100% had a negative influence on cleavage and blastocyst rates (control - 90.13% vs. treated - 82.64% and control - 35.73% vs. treated - 11.57%, respectively, at 24 h of maturation). The 50% FF resulted in embryos with increased inner cell mass numbers (control - 29.91 vs. treated - 35.49, at 24 h of maturation) and total cell numbers (control - 109.53 vs. treated - 120.67, at 26 h of maturation). Even though higher concentration of FF added to the maturation medium reduced embryonic development rates, in lower concentrations, FF slowed the meiotic progression and migration of CG and contributed to increases in inner cell mass number. Thus, FF added to the maturation medium enhances the number of cells in bovine embryos produced in vitro, especially for inner cell mass.
Keywords: embryo development; inner cell mass; In vitro fertilization; Oocytes